Genotipagem do locus ABO (9q34.1) em doadores de sangue da região noroeste do estado de São Paulo - Mattos, Luiz C. (2001)
The advances of molecular genetics enabled us to understand the molecular basis of the ABO locus. Considering Us importance as a genetic marker and its applications, the aim of this study was to verify the distribution of the ABO genotypes in a Brazilian population from the Northwest region of the Sào Paulo Stale, Brazil. The genomic DNA was extracted from three hundred and twenty four healthy Brazilian blood donors (O ] 50; A 118; B 32 and AB 24) and analyzed by PCR amplification followed by restriction enzyme digestion. Fourteen genotypes were identified and the relative frequencies of the O , O , O , A and B genes ivere estimated at 44.6%, 16.9%, 4.1%, 25.3% and 9.1%, respectively. Tloese results demonstrate that the ABO locus presents a high polymorphism as revealed by molecular analysis.